Culture(s) dans la communication professionnelle - Sowa, Magdalena (Neophilologica, 2008)
The objective of the paper is a survey of the possible components of intercultural competence required in professional communication in a foreign language. Effective communication requires a thorough knowledge of not only the language of the interlocutor but also their culture in its various aspects: social customs, proper language standards, company culture etc., all contributing to the overall intercultural competence, and fostering mutual understanding or, when the rules of social and linguistic appropriateness are flouted, leading to misunderstanding. In the paper the problem is illustrated by examples of professional communication in French.